Network Physical Layer Attack in the Very High Capacity Networks - Grenar, David; Frolka, Jakub; Slavicek, Karel; Dostal, Otto; Kyselak, Martin (Advances in electrical and electronic engineering, 2023)
This paper focuses on the analysis of fiber optic line eavesdropping options based on cheap and easy-to-use equipment - for example, the commonly used fiber optic splitters with suitable optical power division ratios. The fiber optic splitter takes a small portion of the optical power sufficient for the eavesdropper to read the data and lets as much signal power as possible pass in the original direction. We attempted to detect the presence of fiber optic splitter-based eavesdropping points on the communication line by using common techniques designated for fiber optic quality measurement and fault detection. The results are summarised in this paper.